The solar-like 'Second Spectrum' and polarized metal lines in the emission of the post-AGB binary 89 Herculis. Issue 2 (4th August 2018) - Leone, F; Gangi, M; Giarrusso, M; Scalia, C; Cecconi, M; Cosentino, R; Ghedina, A; Munari, M; Scuderi, S
ABSTRACT: We studied the polarized spectrum of the post-AGB binary system 89 Herculis on the basis of data collected with the high-resolution Catania Astrophysical Observatory Spectropolarimeter, HArps-North POlarimeter and Echelle SpectroPolarimetric Device for the Observation of Stars. We find the existence of linear polarization in the strongest metal lines in absorption and with low excitation potentials. Signals are characterized by complex Q and U morphologies varying with the orbital period. We rule out magnetic fields, continuum depolarization due to pulsations and hot spots as the possible origin of this 'Second Solar Spectrum'-like behaviour. The linear polarization we detected in the Caii  8662-Å line is clear evidence of optical pumping polarization and rules out scattering polarization from free electrons of the circumbinary environment. In the framework of optical pumping due to the secondary star, the observed periodic properties of the spectral line polarization can be justified by two jets, with a flow velocity of a few tens of km s −1, at the basis of that hourglass structure characterizing 89 Herculis. We also discovered linear polarization across the emission profile of metal lines. Numerical simulations show that these polarized profiles could be formed in an undisrupted circumbinary disc rotating at ≤10 km s −1 and with an orientation in the sky in agreement with optical and radio interferometric results. We conclude that the study of aspherical envelopes, the origin of which is not yet completely understood, of PNe and already present in post-AGBs can benefit from high-resolution spectropolarimetry and that this technique can shape envelopes still too far away for interferometry.